Emergency Response Team (ERT) as an emergency management for campus environment - Sabri, Syikh Sazlin Shah; Mohd. Hussain, Mohd. Ramzi; Ab Sani, Jasasikin; Abdul Hamed, Sapiah; Rusli, Nazrul (Asian Scholars Network, 2023)
Abstract: The emergency preparedness and response plan (EPRP) are a critical system for effectively handling emergencies from various hazards, including the campus of higher education institutions (HEI). The emergencies carry significant risks for employees within their workplace settings and play an integral role in risk management. This paper introduces an Emergency Response Team (ERT) as an emergency management communication for EPRP within the safety management system campus sustainability. It also assesses the ERT's capacity to manage emergencies and involvement in emergencies through the procedure and documentation to optimise emergency preparedness and response. As an organisation, the HEI is encouraged to establish an emergency response team (ERT) and a procedure as essential components of their safety management systems. The paper employs analytical reviews of the related articles to assess the ERT's functions and capacity within the EPRP for the campus sustainability of the HEI. The content analysis is used to analyse the literature review of the article. The findings revealed that an Emergency Response Team (ERT) for campus sustainability plays a crucial role in ensuring the environmental well-being and resilience of a university or college campus. This specialised team addresses and mitigates sustainability-related emergencies, such as natural disasters, environmental hazards, or infrastructure failures. Their primary goal is to safeguard the campus's sustainable infrastructure, promote eco-friendly practices, and coordinate disaster preparedness and response efforts to minimise environmental damage, support the well-being of the campus community, and maintain a commitment to long-term sustainability goals. Keywords: Emergency Preparedness Response Plan (EPRP), Emergency Response Team (ERT), Safety Management System (SMS)